2022
DOI: 10.1029/2021ja030157
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of E‐Region Near Range Echoes Partially Modulated by F‐Region Traveling Ionospheric Disturbances Observed by the Same SuperDARN HF Radar

Abstract: We present the first observations from SuperDARN HF radar data of E‐region Near Range Echoes (NREs) whose amplitudes are partially modulated by Medium‐Scale Traveling Ionospheric Disturbances (MSTIDs) propagating in the F‐region overhead that have been observed by the same radar in the far ranges. SuperDARN NREs occur normally ∼180–315 km downrange from the radar at ∼95–125 km altitude. Selected observations of TID‐modulated NREs are presented from SANAE and Zhongshan Antarctic SuperDARN radars for both summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 82 publications
(201 reference statements)
5
21
0
Order By: Relevance
“…The long-term statistical study shows that the mean and standard deviation of the Spearman correlation coefficient values is 0 and 0.3, respectively indicating that the positive and negative Spearman correlation coefficient values where MSTIDs partially affected NREs, that is, by ∼9%, are almost equal. These values agree well with the previous studies (Hiyadutuje et al, 2022;Otsuka et al, 2007Otsuka et al, , 2009.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The long-term statistical study shows that the mean and standard deviation of the Spearman correlation coefficient values is 0 and 0.3, respectively indicating that the positive and negative Spearman correlation coefficient values where MSTIDs partially affected NREs, that is, by ∼9%, are almost equal. These values agree well with the previous studies (Hiyadutuje et al, 2022;Otsuka et al, 2007Otsuka et al, , 2009.…”
Section: Discussionsupporting
confidence: 94%
“…To maintain divergence-free current continuity for the Pedersen current J in F-region, a periodic horizontal polarization electric field (E pF = [δΣ p /Σ p ] (E + U × B)[k/|k|]) takes place within the MSTID wave. Figure 7 of Hiyadutuje et al (2022) shows the polarization electric field generated by a passing MSTID wave. The Pedersen current is given by J = Σ p (E + U × B), where Σ p is the F-region Pedersen conductance, E is the electric field, U is the neutral wind and B is the magnetic field (Haldoupis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that coupling between the E and the F regions and sporadic-E layers can augment and enhance the instabilities associated with MSTIDs (Ogawa et al, 2009;Otsuka et al, 2007). Hiyadutuje et al (2022) examined the relation between far-range and near-range echoes observed by SuperDARN and suggested that MSTIDs in the F region can partially modulate an existing Gradient Drift Instability in the E region. Overall, strong coupling between the E and F regions of the ionosphere was observed during certain MSTID intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Hiyadutuje et al. (2022) examined the relation between far‐range and near‐range echoes observed by SuperDARN and suggested that MSTIDs in the F region can partially modulate an existing Gradient Drift Instability in the E region. Overall, strong coupling between the E and F regions of the ionosphere was observed during certain MSTID intervals.…”
Section: Discussionmentioning
confidence: 99%